Iron-modified biochar modulates root metabolism, mitigates antimony accumulation and enhances growth in rice (Oryza sativa) - Renyan Duan; Fumin Meng; Hui Yang; Yihuan Du; Qian Dai; Yu Zhang (BMC Plant Biology)
Abstract Background Antimony (Sb), with low biodegradability and high bioavailability in plants, poses significant health risks via the food chain due to its chronic toxicity and carcinogenicity. Modified biochar represents a promising amendment for ecological remediation of metal-contaminated croplands, yet the efficacy and mechanisms of its application in mitigating Sb accumulation and improving plant growth in Sb-polluted agricultural systems remain inadequately elucidated and require systematic investigation. Results In this study, pristine biochar (BC) and iron-modified biochar (FeBC) were prepared from pomelo peel flesh (PPF; Citrus maxima), and their effects on rice root growth, Sb content, and metabolism under 30 mg/L Sb stress were evaluated. Treatment with 5 g/L BC and 5 g/L FeBC increased root length by 35.04% and 84.60%, respectively, while reducing Sb accumulation in roots by 25.79% and 28.03%, respectively. Root metabolite analysis showed that, compared to BC, FeBC significantly decreased levels of p-coumaroylagmatine, silibinin, and osmanthuside A by 75%, 37%, and 37%, respectively. Conversely, FeBC elevated levels of (S)-actinidine, phaeophorbide A, and 2-keto-6-acetamidocaproate by 187%, 156%, and 122%, respectively. These altered metabolites were enriched in five key metabolic pathways: phenylalanine, tyrosine, and tryptophan biosynthesis; phenylalanine biosynthesis; lysine degradation; tryptophan metabolism; and pantothenate and CoA biosynthesis. Correlation analysis demonstrated significant interrelationships among biochar-induced metabolites, root growth, and Sb accumulation dynamics under Sb stress. Conclusions The findings provided the insights that FeBC enhanced rice root metabolism and growth while reducing root Sb accumulation. This study provided a methodological foundation for developing eco-friendly remediation technologies in Sb-contaminated soils to enable safer and more sustainable rice production. Graphical abstract